Laser Treatment of Hemangiomas, Oral Cysts, and Mucocele: Advances in Minimally Invasive Oral and Maxillofacial Surgery - Khalilova, Barchinoy Rasulovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
Laser-assisted surgical techniques have emerged as a highly effective, minimally invasive approach for the management of soft-tissue lesions in oral and maxillofacial surgery, particularly hemangiomas, oral mucoceles, and small odontogenic or non-odontogenic cysts. These pathologies are frequently encountered in daily clinical practice and often require precise excision with minimal bleeding, reduced tissue trauma, and rapid healing. The purpose of this extended abstract is to provide a comprehensive synthesis of current evidence regarding the application of diode and CO₂ laser systems in treating these lesions, highlighting clinical efficacy, safety, procedural advantages, and outcome predictability in comparison to conventional surgical methods.